2004
DOI: 10.1103/physrevb.69.024109
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of theCuGaO2delafossite under high pressure

Abstract: We have performed pseudopotential calculations and x-ray-diffraction and x-ray-absorption measurements on the CuGaO 2 delafossite under high pressure. We have completely characterized the structural behavior of the low pressure phase. We have found out that the a axis is more compressible than the c axis, and as a consequence the oxygen octahedra defined by the gallium environment tend to become more regular under high pressure. We have determined the internal parameter describing the oxygen position inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 20 publications
6
31
0
Order By: Relevance
“…Figure 5 shows the composition-dependent Raman spectra of single phase of CuFe 1−x Sc x O 2 (0 ≤ x ≤ 0.25) at room temperature. All the samples showed two Raman active modes in agreement with earlier results on CuFeO 2 [26] and CuCrO 2 [27], CuGaO 2 [25]. These bands are identified as σ (A 1g ) at 692 cm −1 and σ (E g ) at 351 cm −1 , respectively, and it has been suggested that these vibrations may be associated with the spectral features of edge-sharing Fe III O 6 octahedra and possibly the O-Cu − -O linear bond [28].…”
Section: Raman Spectroscopysupporting
confidence: 79%
See 1 more Smart Citation
“…Figure 5 shows the composition-dependent Raman spectra of single phase of CuFe 1−x Sc x O 2 (0 ≤ x ≤ 0.25) at room temperature. All the samples showed two Raman active modes in agreement with earlier results on CuFeO 2 [26] and CuCrO 2 [27], CuGaO 2 [25]. These bands are identified as σ (A 1g ) at 692 cm −1 and σ (E g ) at 351 cm −1 , respectively, and it has been suggested that these vibrations may be associated with the spectral features of edge-sharing Fe III O 6 octahedra and possibly the O-Cu − -O linear bond [28].…”
Section: Raman Spectroscopysupporting
confidence: 79%
“…Since there is only one mode of each symmetry, the exact eigenvector is determined without any lattice dynamical model required. Pellicer-Porres et al [25] had discussed the phonon dispersion at the zone center for CuGaO 2 delafossite. They proposed that the inversion center is lost along the direction of (T ) direction and the symmetry is reduced from D 3d to C 3v .…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Ab-initio band structure calculations and optical absorption measurements on CuAlO 2 and CuScO 2 thin films indicate the stability of CuAlO 2 , an indirect band gap semiconductor upto 20 GPa whereas CuScO 2 shows phase transition beyond 13 GPa to an unidentified phase [35]. Calculated phonon frequencies for CuGaO 2 and CuAlO 2 under pressure have indicated the dynamical instability of a transverse acoustic phonon to be the cause of pressure induced phase transition [27,28] in these materials. Recent first principles calculations determined the critical pressure of transition for delafossite CuAlO 2 to a leaning delafossite with a higher band gap, to be 60…”
Section: Introductionmentioning
confidence: 99%
“…Raman scattering measurements on CuAlO 2 [27] and CuGaO 2 [28] have reported that these compounds transform to unresolved structures above 34 and 26 GPa respectively. Energy dispersive x-ray diffraction and in-situ x-ray absorption near edge structure (XANES) measurements on CuGaO 2 under pressure confirm changes in copper environment leaving the environment of other cation unchanged [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation